AKTIVITAS ANTIOKSIDAN PADA MINUMAN FUNGSIONAL DARI EKSTRAK DAGING KERANG LENTERA (Lingula unguis) - Ahmad Fauzan Lubis (Jurnal Ilmu Kesehatan Abdurrab, 2024)
ABSTRACT The use of natural ingredients as a source of natural antioxidants in making healthy foods and drinks, supplements and medicines continues to grow. The antioxidants produced by the human body are not enough to fight excessive free radicals in the body, for this reason the body needs antioxidant intake from outside. It is very possible for lamp shell to be developed as healthy food and drink products, supplements and medicines because shellfish are a source of vitamin B12 and an important nutrient for health. This research was conducted to determine the best formulation of the lantern clam herbal drink and to determine the antioxidant content of the lantern clam herbal drink. The method used in this research consists of 4 stages. Phase I is the preparation of raw materials and the manufacture of lantern shellfish extract. Phase II Testing Brine Shrimp Lethality Test (BSLT). Phase III research is making herbal drinks from lantern clam meat extract and determining the best formulation of the herbal drink through a hedonic test and phase IV research is antioxidant testing of the best formulation to determine the antioxidant content in the lantern clam herbal drink. The research results showed that the best formula for herbal drinks based on consumer acceptance tests was F3 (30%) with 30% lantern clam meat extract formula. The antioxidant activity content of the best formulation is with an LC50 value of 74.30 with strong antioxidant activity where the IC50 is 51-100 ppm. Keywords: lamp shell, herbal drink, antioxcidant